2023
DOI: 10.11591/ijece.v13i4.pp4516-4525
|View full text |Cite
|
Sign up to set email alerts
|

The role of neural network for estimating real estate prices value in post COVID-19: a case of the middle east market

Abstract: The main goal of this paper was to explore the use of an artificial neural network (ANN) model in predicting real estate prices in the Middle East market. Although conventional modeling approaches such as regression can be used in prediction, they have a weakness of a predetermined relationship between input and output. In this regard, using the ANN model was expected to reduce the bias and ensure non-linear relationships are also covered in the prediction process for more accurate results. The ANN model was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The strategy ensures that participants are not victimized based on their opinions expressed in the study. For this study, confidentiality was defined as restricting access to interview data by storing them in computer files with solid passwords [34][35][36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…The strategy ensures that participants are not victimized based on their opinions expressed in the study. For this study, confidentiality was defined as restricting access to interview data by storing them in computer files with solid passwords [34][35][36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…While many studies have focused on property-specific and spatial features, the integration of macroeconomic and temporal factors has been relatively limited. The studies in [12,15] acknowledged the importance of considering macroeconomic factors and other influential variables, such as interest rates, construction costs, and disposable income, which can significantly impact real estate prices. Addressing this gap by incorporating relevant macroeconomic and temporal features aligns with the research objective of developing comprehensive predictive models for the UK real estate market.…”
Section: Macroeconomic and Temporal Factorsmentioning
confidence: 99%
“…Several studies have highlighted challenges related to data availability and technological complexity in implementing advanced predictive models. The studies in [9,15,16] discussed limitations in accessing high-quality, up-to-date datasets and the complexities involved in deploying sophisticated ML techniques. The studies in [7,17] reported relatively high RMSE values in their prediction models, indicating room for improvement in model accuracy.…”
Section: Data Availability and Technological Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a moment in history when the interaction between microeconomic and macroeconomic events is extremely strong because of the globally impactful events in the recent years of the COVID-19 pandemic [30] and the Ukraine war outbreak [31]. Several consequences have involved the financial [32][33][34] and energetic [35][36][37] sectors, with evident repercussions on the real estate sector, such as higher offer rigidity, changes in demand preferences, and increases in the costs of construction, therefore ultimately affecting property prices [38].…”
Section: Defining Of the Real Estate Market Segmentmentioning
confidence: 99%